TRANSFORMATIONAL LEADERSHIP WHICH CAN GROW ORGANIZATIONAL COMMITMENT - Betty Yuliani Silalahi (Jurnal Psikologi, 2008)
A meta-analysis consist of 45 studies from 20 articles and 20860 subjects evaluated the correlation between Transformational leadership and Organizational commitment. Summary analysis provided support for the hypothesis that transformational leadership has a correlation on organizational commitment. The purpose of the study is to analyzed the data from the primer study and to support the hypothesis or refuse from the studies. Result indicated that transformational leadership can grow organizational commitment.Keywords : Transformational leadership, Organizational Commitment, Meta Analysis